Sex Workers Still Human? Reading Dehumanization in Photo-Journalism - Farida, Farida; Garry Brumadyadisty; Rendy Agung Prakoso; Nurul Suhesti, Nurul Suhesti; Hartopo Eko Putro (CV. AFDIFAL MAJU BERKAH, 2025)
Photojournalism serves as a powerful medium in shaping societal perceptions, particularly in the representation of marginalized communities. This study critically examines how sex workers are visually portrayed in photojournalism, employing a semiotic analysis grounded in the frameworks of Ferdinand de Saussure, Charles Sanders Peirce, and Roland Barthes. The research investigates the role of denotation and connotation in constructing meaning, while foregrounding the mechanisms of dehumanization. Dehumanization is explored through both overt visual techniques and more subtle compositional choices that strip subjects of agency and individuality. Utilizing qualitative content analysis, the study analyzes a selection of photojournalistic images, focusing on signs, codes, and symbolic structures embedded within the visuals. Findings indicate a prevalent reliance on visual tropes that perpetuate stereotypes and reinforce social hierarchies. These visual strategies not only marginalize sex workers but also align with broader patterns of social exclusion and discrimination. The study concludes that ethical considerations in visual storytelling remain critically underexplored, especially in the context of vulnerable populations. Addressing these issues requires a reevaluation of journalistic practices and the incorporation of humanizing visual narratives that affirm dignity and complexity. This research contributes to media studies by bridging semiotic theory with critical discourse on visual ethics and human rights